Biliary transporter gene mutations in severe intrahepatic cholestasis of pregnancy: Diagnostic and management implications. Issue 2 (6th August 2018) - Yeap, Sze Pheh; Harley, Hugh; Thompson, Richard; Williamson, Kate Diana; Bate, John; Sethna, Farah; Farrell, Geoffrey; Hague, William "Bill"
Abstract: Background and Aims: Clinical syndromes associated with biallelic mutations of bile acid (BA) transporters usually present in childhood. Subtle mutations may underlie intrahepatic cholestasis of pregnancy (ICP) and oral contraceptive steroid (OCS) induced cholestasis. In five women with identified genetic mutations of such transporters, with eight observed pregnancies complicated by ICP, we examined relationships between transporter mutations, clinical phenotypes, and treatment outcomes. Methods: Gene mutation analysis for BA transporter deficiencies was performed using Next Generation/Sanger sequencing, with analysis for gene deletions/duplications. Results: Intrahepatic cholestasis of pregnancy was early‐onset (9–32 weeks gestation) and severe (peak BA 74–370 μmol/L), with premature delivery (28 +1 –37 0 weeks gestation) in 7/8 pregnancies, in utero passage of meconium in 4/8, but overall good perinatal outcomes, with no stillbirths. There was generally no response to ursodeoxycholic acid and variable responses to rifampicin and chelation therapies; naso‐biliary drainage appeared effective in 2/2 episodes persisting post‐partum in each of the two sisters. Episodic jaundice occurring spontaneously or provoked by non‐specific infections, and OCS‐induced cholestasis, had previously occurred in 3/5 women. Two cases showed biallelic heterozygosity for several ABCB11 mutations, one was homozygous for an ABCB4 mutation and a fourth case was heterozygous for another ABCB4 mutation. Conclusions: Early‐onset or recurrent ICP, especially with previous spontaneous or OCS‐induced episodes of cholestasis and/or familial cholestasis, may be attributable to transporter mutations, including biallelic mutations of one or more transporters. Response to standard therapies for ICP is often incomplete; BA sequestering therapy or naso‐biliary drainage may be effective. Optimized management can produce good outcomes despite premature birth and evidence of fetal compromise.